Microstructure evaluation of CO-222/SiC coating produced by the plasma spraying method. (4th March 2018) - Jafari, M.; Mostaghimi, J.; Monajatizadeh, H.; Rafiei, M.
ABSTRACT: A composite coating containing 10 wt-% of SiC and 90 wt-% CO-222 super alloy was coated with atmospheric plasma spray at two different currents on the surface of the 304 stainless steel. The aim of this research is to address the microstructure and phase formation during the plasma spray of Co-222/SiC composite coatings. The phase analysis, microstructure, surface morphology and microhardness of Co-222/SiC feedstock powder and the coating were characterised by X-ray diffraction, field emission scanning electron microscopy and Vickers microhardness. The results demonstrated that the outer surface of SiC particles was decarburised and the SiO2 phase was formed at the high temperature of plasma gun. Also, Cr2 O3 oxide was formed owing to the reaction of Cr from Co-222 super alloy with O2 . By the formation of oxide phases and degradation of silicon carbide, the microhardness of the composite was reduced, as compared to CO-222 super alloy.